Emerging Trends in the Formation and Function of Tuberculosis Granulomas - Lugo-Villarino, Geanncarlo; Hudrisier, Denis; Benard, Alan; Neyrolles, Olivier (Frontiers in Immunology, 2013)
The granuloma is an elaborated aggregate of immune cells found in non-infectious as well as infectious diseases. It is a hallmark of tuberculosis (TB). Predominantly thought as a host-driven strategy to constrain the bacilli and prevent dissemination, recent discoveries indicate the granuloma can also be modulated into an efficient tool to promote microbial pathogenesis. The aim of future studies will certainly focus on better characterization of the mechanisms driving the modulation of the granuloma functions. Here, we provide unique perspectives from both the innate and adaptive immune system in the formation and the role of the TB granuloma. As macrophages (Mϕs) comprise the bulk of granulomas, we highlight the emerging concept of Mϕ polarization and its potential impact in the microbicide response, and other activities, that may ultimately shape the fate of granulomas. Alternatively, we shed light on the ability of B cells to influence inflammatory status within the granuloma.